Transdiciplinary Approach to Making Science-Based Transgenic Products Policy Recommendations - Agus Pakpahan (Analisis Kebijakan Pertanian, 2012)
The Government Regulation No. 21, 2005 of biosafety for genetically engineered products considers aspects of religions, ethics and aesthetics in its policy recommendations and produces recommendations based on the precautionary principle and justifiable scientific methods. The formula developed by Choi (2005) was provided as an example of a science-based policy recommendation making process. Since solving a certain problem cannot be done without regarding the possible emergence of new problems, a transdisciplinary knowledge-based recommendation making will provide better outcome. The general conclusion is that we need to develop our institutional capacity in order to be able to apply a method of policy recommendation making process in the format of transdiciplinary approach to making science-based transgenic products policy recommendations.